2013
DOI: 10.1038/aps.2012.182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the HDAC inhibitor vorinostat on the osteogenic differentiation of mesenchymal stem cells in vitro and bone formation in vivo

Abstract: Vorinostat, known as a potent anti-myeloma drug, stimulates MSC osteogenesis in vitro. With the optimized treatment regimen, any decrease in bone formation was not observed in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 42 publications
3
45
2
Order By: Relevance
“…Nevertheless, our observations appear to be in contrast with previous works in which a positive effect of these drugs on RUNX2 expression was reported in skeletal cells (43,44). Currently, there are no experimental data to explain such discrepancy, but the different cellular context is likely to play a relevant role.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, our observations appear to be in contrast with previous works in which a positive effect of these drugs on RUNX2 expression was reported in skeletal cells (43,44). Currently, there are no experimental data to explain such discrepancy, but the different cellular context is likely to play a relevant role.…”
Section: Discussioncontrasting
confidence: 99%
“…Selective targeting and lower doses (10-100x lower) of HDACi have been shown to be better tolerated in animal models and have different effects on bone cells without the induction of apoptosis. This is supported by a recent in vitro study demonstrating that higher doses of vorinostat induced apoptosis of mesenchymal stem cells, but was not observed when lower doses were used [78].…”
Section: General Effects Of Hdaci On Bone Formationsupporting
confidence: 52%
“…Paradoxically, while osteoblast numbers were reduced in vorinostat treated bones, measures of osteoblast activity such as mineral apposition rate and bone formation rate were elevated. In vitro studies showed that immature osteoblasts were highly susceptible to DNA damage and cell cycle arrest when cultured in the presence of vorinostat [89, 90]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the direct effects of the drugs on precursor cells remain a concern for in vivo bone regeneration [75]. Although some studies suggest that systemic administration of vorinostat at lower doses or reduced frequency may prevent the adverse skeletal effects of HDI therapy [90], finding an effective dose of a broad acting histone modifying drug that has no effects on a renewing tissue like bone, blood, or gastric epithelium may be impossible, just as it is for many cancer therapies, including chemotherapy and hormone-deprivation, and anti-inflammatory medications (e.g., corticosteroids). One way to address this problem is to gain a better understanding of which epigenetic modulators (readers, writers, and erasers) are expressed in bone cells so that more specific inhibitors can be designed for specific diseases.…”
Section: Introductionmentioning
confidence: 99%